APLIKASI GAME PETUALANGAN SI KANCIL BERBASIS ANDROID - Erin masfufah; M Ghofar Rohman; Purnomo Hadi Susiolo (Universitas Islam Lamongan, 2017)
Games are actually very important for the development of the human brain because a human will start thinking when faced with a problem. While in a game, the user is faced with various problems and required to solve them so that the user can finish or even win the game being played. The purpose of this research is to make adventure genred game with educational content and change the paradigm of the most users about the character of Kancil who is famous by stealing cucumbers because in this game Kancil is portrait trying to collect coins and find golden cucumbersby passing various obstacles on his way. This game is made using Construct 2 application and presented with visual media images completed with good sound to make this game more interesting. This game is as a medium of entertainment. This game is presented in the form of 2d game with .apkformat in Android based system. This game is made and given to the users for its usability testing by using questionnaire. This game is very feasible to use in accordance with the final percentage of 91,1%.